1998
DOI: 10.1103/physrevb.58.5632
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic transition inMnn(n=28)clusters

Abstract: Theoretical electronic structure studies on Mn n (nϭ2 -8) clusters have been carried out using a linearcombination-of-atomic-orbitals-molecular-orbital approach within the density-functional formalism. It is shown that Mn 2 and Mn 3 have energetically close ferromagnetic and antiferromagnetic or frustrated antiferromagnetic solutions. Mn 4 , Mn 5 , Mn 6 , Mn 7 , and Mn 8 are all ferromagnetic with moments of 20, 23, 26, 29, and 32 B . The appearance of ferromagnetic character is shown to be accompanied by bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
99
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 25 publications
11
99
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The magnetic ordering of the Mn 2 dimer is very sensitive to interatomic separation, [1][2][3] while clusters containing 3-5 Mn atoms are all predicted to have ferromagnetic ground states with magnetic moments of ∼5 μ B /atom. 2,4,5 Mn 6 and Mn 7 are ferrimagnetic, 5,9 and there is a distinct transition from high-to low-spin configurations in Mn n clusters with n ≥ 7. 5 In all anionic clusters, Mn − n (n = 2-8), the preferred ordering is ferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8] The magnetic ordering of the Mn 2 dimer is very sensitive to interatomic separation, [1][2][3] while clusters containing 3-5 Mn atoms are all predicted to have ferromagnetic ground states with magnetic moments of ∼5 μ B /atom. 2,4,5 Mn 6 and Mn 7 are ferrimagnetic, 5,9 and there is a distinct transition from high-to low-spin configurations in Mn n clusters with n ≥ 7. 5 In all anionic clusters, Mn − n (n = 2-8), the preferred ordering is ferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…11 They found that the ferromagnetic states of Mn 5 and Mn 6 are destabilized by the addition of oxygen, and the overall magnetic moment is reduced compared to pure Mn n clusters. Another conclusion of this work was the identification of several nearly degenerate "isomags."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) The 3d 5 4s 2 atomic electronic configuration makes Mn 2 very weakly bonded with van der Waals interaction and the nature of the magnetic coupling in the dimer is still disputed. In bulk, manganese has the lowest cohesive energy (2.92 eV/atom) and large compressibility among the 3d metals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Recent experiments on Mn clusters with 11-99 atoms show magnetically ordered clusters with significantly reduced moments and a maximum value of about 1.4 µ B /atom. 3) This is close to the magnetic moments of about 1 µ B in bulk Mn.…”
Section: Introductionmentioning
confidence: 99%